Shexiang Tongxin Dropping Pills Promote Macrophage Polarization-Induced Angiogenesis Against Coronary Microvascular Dysfunction via PI3K/Akt/mTORC1 Pathway - Lu, Xiangyu; Yao, Junkai; Li, Changxiang; Cui, Lingwen; Liu, Yizhou; Liu, Xiangning; Wang, Gang; Dong, Jianteng; Deng, Qiong; Hu, Yueyao; Guo, Dongqing; Wang, Wei; et al. (Frontiers in Pharmacology, 2022)
Background: Accumulating evidence suggests that coronary microvascular dysfunction (CMD) is one of the important causes of coronary artery diseases. Angiogenesis can effectively improve CMD by increasing blood supply capacity, recovering cardiac function and poor haemodynamics. Clinical studies have approved Shexiang Tongxin Dripping Pills (STDP) exerted remarkable roles on ameliorating CMD, but the effects and mechanisms of STDP on angiogenesis have not been clarified. Purpose: The purpose of this study was to elucidate the effects and potential mechanisms of STDP on macrophage polarization-induced angiogenesis against CMD. Methods: Echocardiography, optical microangiography (OMAG) and histological examination were applied to evaluate cardioprotection and pro-angiogenic effects of STDP on left anterior descending (LAD) ligation-induced CMD rats. In vitro, oxygen-glucose deprivation-reperfusion (OGD/R)-induced HUVECs model and LPS-stimulated BMDMs model were established to observe the effects of STDP on angiogenesis and M2 macrophage polarization. Results: STDP improved cardiac function, increased microvascular density and the number of M2 macrophages in the heart of CMD rats. In vitro, STDP accelerated the proliferation, migration and tube-formation in OGD/R-induced HUVECs as similar as the effects of VEGF-A. Furthermore, in LPS-stimulated BMDMs model, STDP modulated M2 macrophage polarization and increased VEGF-A release via PI3K/AKT/mTORC1 pathway. Conclusion: STDP promoted macrophage polarization-induced angiogenesis against CMD via PI3K/Akt/mTORC1 pathway. Our results demonstrated that the phenotype transformation of macrophages and stimulating the secretion of VEGF-A may be applied as novel cardioprotective targets for the treatment of CMD.